The Turing Bombe Victory and the first naval Enigma decrypts. Issue 4 (4th July 2017) - Wright, John
ABSTRACT: Victory was the name of the first prototype Bombe that was developed for breaking the German Enigma messages of World War II. It lacked the diagonal board and simultaneous scanning that was provided for all the later models, but these disadvantages were overcome by the ingenious use of a column menu (a special Bombe menu where the Enigma fast rotors are all in the same position) to break six days of naval traffic, 22–27 April 1940, following the pinch of material from an armed trawler Schiff 26 ( Polares ). These were the first naval decrypts of the War, and their solution took several months to complete. No further naval breaks occurred until November. This article examines the decryption process in some detail in order to explain the difficulties, highlight the role of Victory in this process, and provide detailed workings of the processes. It also sheds some light on the early development of the British Bombe.